HUBUNGAN STATUS GIZI DENGAN GOUT ARTHRITIS PADA LANJUT USIA DI PUSKESMAS WAWONASA MANADO - Lumunon, Oktavina J; Bidjuni, Hendro; Hamel, Rivelino (Universitas Sam Ratulangi, 2015)
Abstract :Gout Arthritis is a disease that occurs due to a chronic increase in uric acid concentration I in plasma. Gout is a buildup of uric acid in the body and abnormalities in purine metabolism. Nutritional status is a state body that is the end result of a balance between nutrients into the body and utilasinya. Nutritional status is a state of the body as a result of food consumption and use of nutrients. The purpose of this study is to determine whether there is a relationship with gouty arthritis nutritional status of the elderly in Puskesmas Wawonasa Manado. The study design was observational analytic method with cross sectional design. The population in this study were all elderly who visit the health center Wawonasa Manado. Samples in this study using a sampling technique is determined purposively (purposive sampling). The sample was total population of 60 people with the details of 45 women and 15 men. The data is processed using univariate and bivariate by using SPSS (Statistic Program for Social Science) through Chi Square calculation at 95% significance level (á0,05). Results of this study showed no association between nutritional status and gouty arthritis because the value obtained ñ 0.048. The conclusion of this study is that there is a relationship between nutritional status and gouty arthritis in the elderly in Puskesmas Wawonasa Manado. Suggestions in this study for the elderly are advised to check regularly gouty arthritis / once a month. Keywords: Nutritional Status, Gout arthritis. Abstrak :Gout Arthritis adalah penyakit yang terjadi akibat adanya peningkatan kronis konsentrasi asam urat I dalam plasma. Gout merupakan terjadinya penumpukan asam urat dalam tubuh dan terjadi kelainan metabolism purin.Status gizi adalah keadaan tubuh yang merupakan hasil akhir dari keseimbangan antara zat gizi yang masuk ke dalam tubuh dan utilasinya.Status gizi adalah keadaan tubuh sebagai akibat konsumsi makanan dan penggunaan zat-zat gizi.Tujuan penelitian ini yaitu untuk mengetahui apakah terdapat hubungan status gizi dengan gout arthritis pada lanjut usia di Puskesmas Wawonasa Manado. Desainpadapenelitian iniadalahmetode observasional analitik dengan rancangan cross sectional. Populasi adalah seluruh lanjut usia yang berkunjung di Puskesmas Wawonasa Manado. Sampel menggunakan teknik pengambilan sampel ditentukan secara purposif (purposive sampling). Sampel penelitian ini adalah total populasi yang berjumlah 60 orang dengan rincian perempuan 45 orang dan laki-laki 15 orang. Data diolah secara univariat dan bivariat dengan menggunakan program SPSS (Statistic Program for Social Science) melalui perhitungan Chi Square pada tingkat kemaknaan 95% (á0,05). Hasil menunjukkan, ada hubungan antara status gizi dengan gout arthritis karena nilai yang diperoleh ñ 0,048.Kesimpulan dalam penelitian ini adalah ada hubungan antara status gizi dengan gout arthritis pada lanjut usia di wilayah kerja Puskesmas Wawonasa Manado. Saran bagi lanjut usia disarankan untuk melakukan pemeriksaan gout arthritis secara rutin/sebulan sekali. Kata Kunci : Status Gizi, Gout arthritis.